Ochrona wiedzy w dobie globalizacji : wybrane zagadnienia - Rowińska-Fronczek, Mariolanta (The knowledge protection in the time of globalisation: selected questions, 2005)
In the time of globalisation, the knowledge protection is necessary and requires to prepare wellthought- out effective strategy of protection. It is especially important for the firms which have expensive R&D. One of the ways of the knowledge protection - which prevents undesirable benchmarking - is a patent system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 93-101